Impact of streptozotocin on altering normal glucose homeostasis during insulin testing in diabetic rats compared to normoglycemic rats - Qinna NA; Badwan AA (Dove Medical Press, 2015)
Nidal A Qinna,1 Adnan A Badwan2 1Department of Pharmacology and Biomedical Sciences, Faculty of Pharmacy and Medical Sciences, University of Petra, 2Research and Innovation Centre, The Jordanian Pharmaceutical Manufacturing Co. Plc. (JPM), Amman, Jordan Abstract: Streptozotocin (STZ) is currently the most used diabetogenic agent in testing insulin and new antidiabetic drugs in animals. Due to the toxic and disruptive nature of STZ on organs, apart from pancreas, involved in preserving the body’s normal glucose homeostasis, this study aims to reassess the action of STZ in inducing different glucose response states in diabetic rats while testing insulin. Diabetic Sprague-Dawley rats induced with STZ were classified according to their initial blood glucose levels into stages. The effect of randomizing rats in such a manner was investigated for the severity of interrupting normal liver, pancreas, and kidney functions. Pharmacokinetic and pharmacodynamic actions of subcutaneously injected insulin in diabetic and nondiabetic rats were compared. Interruption of glucose homeostasis by STZ was challenged by single and repeated administrations of injected insulin and oral glucose to diabetic rats. In diabetic rats with high glucose (451–750 mg/dL), noticeable changes were seen in the liver and kidney functions compared to rats with lower basal glucose levels. Increased serum levels of recombinant human insulin were clearly indicated by a significant increase in the calculated maximum serum concentration and area under the concentration–time curve. Reversion of serum glucose levels to normal levels pre- and postinsulin and oral glucose administrations to STZ diabetic rats were found to be variable. In conclusion, diabetic animals were more responsive to insulin than nondiabetic animals. STZ was capable of inducing different levels of normal glucose homeostasis disruption in rats. Both pharmacokinetic and pharmacodynamic actions of insulin were altered when different initial blood glucose levels of STZ diabetic rats were selected for testing. Such findings emphasize the importance of selecting predefined and unified glucose levels when using STZ as a diabetogenic agent in experimental protocols evaluating new antidiabetic agents and insulin delivery systems. Keywords: protein delivery, animal model, diabetes mellitus, experimental, antidiabetic agents, streptozotocin